Usefulness of matrix‐assisted laser desorption ionisation–time‐of‐flight mass spectrometry for identifying clinical Trichosporon isolates. (16th January 2014) - de Almeida Júnior, J. N.; Figueiredo, D. S. Y.; Toubas, D.; Del Negro, G. M. B.; Motta, A. L.; Rossi, F.; Guitard, J.; Morio, F.; Bailly, E.; Angoulvant, A.; Mazier, D.; Benard, G.; et al.
Abstract Trichosporon spp. have recently emerged as significant human pathogens. Identification of these species is important, both for epidemiological purposes and for therapeutic management, but conventional identification based on biochemical traits is hindered by the lack of updates to the species databases provided by the different commercial systems. In this study, 93 strains, or isolates, belonging to 16 Trichosporon species were subjected to both molecular identification using IGS1 gene sequencing and matrix‐assisted laser desorption ionisation–time‐of‐flight (MALDI–TOF) analysis. Our results confirmed the limits of biochemical systems for identifying Trichosporon species, because only 27 (36%) of the isolates were correctly identified using them. Different protein extraction procedures were evaluated, revealing that incubation for 30 min with 70% formic acid yields the spectra with the highest scores. Among the six different reference spectra databases that were tested, a specific one composed of 18 reference strains plus seven clinical isolates allowed the correct identification of 67 of the 68 clinical isolates (98.5%). Although until recently it has been less widely applied to the basidiomycetous fungi, MALDI–TOF appears to be a valuable tool for identifying clinical Trichosporon isolates at the species level.